Ervilia castanea (Mollusca, Bivalvia) populations adversely affected at CO2 seeps in the North Atlantic - Marta, Martins (2021)
Sites with naturally high CO2 conditions provide unique opportunities to forecast the vulnerability of coastal ecosystems to ocean acidification, by studying the biological responses and potential adaptations to this increased environmental variability. In this study, we investigated the bivalve Ervilia castanea in coastal sandy sediments at reference sites and at volcanic CO2 seeps off the Azores, where the pH of bottom waters ranged from average oceanic levels of 8.2, along gradients, down to 6.81, in carbonated seawater at the seeps. The bivalve population structure changed markedly at the seeps. Large individuals became less abundant as seawater CO2 levels rose and were completely absent from the most acidified sites. In contrast, small bivalves were most abundant at the CO2 seeps. We propose that larvae can settle and initially live in high abundances under elevated CO2 levels, but that high rates of post-settlement dispersal and/or mortality occur. Ervilia castanea were susceptible to elevated CO2 levels and these effects were consistently associated with lower food supplies. This raises concerns about the effects of ocean acidification on the brood stock of this species and other bivalve molluscs with similar life history traits.